Reseña de :Núñez Martínez, Juan Jacobo; Belda Calvo, Pedro Javier. Marketing Jurídico, Editorial Thomson Reuters Proview, Madrid, 2016. - Goig Martínez, Juan Manuel (Revista de Derecho de la UNED (RDUNED), 2016)
-